Two Splice Isoforms of Leptinotarsa Ecdysis Triggering Hormone Receptor Have Distinct Roles in Larva-Pupa Transition - Shen, Chen-Hui; Xu, Qing-Yu; Fu, Kai-Yun; Guo, Wen-Chao; Jin, Lin; Li, Guo-Qing (Frontiers in Physiology, 2020)
Insect ecdysis triggering hormone (ETH) receptors (ETHRs) are rhodopsin-like G protein-coupled receptors. Upon binding its ligand ETH, ETHR initiates a precisely programed ecdysis behavior series and physiological events. In Drosophila melanogaster, the ethr gene produces two functionally distinct splicing isoforms, ethra and ethrb. ETH/ETHRA activates eclosion hormone (EH), kinin, crustacean cardioactive peptide (CCAP) and bursicon (burs and pburs) neurons, among others, in a rigid order, to elicit the behavioral sequences and physiological actions for ecdysis at all developmental stages, whereas ETH/ETHRB is required at both pupal and adult ecdysis. However, the role of ETHRB in regulation of molting has not been clarified in any non-drosophila insects. In the present paper, we found that 20-hydroxyecdysone (20E) signaling triggers the expression of both ethra and ethrb in a Coleopteran insect pest, the Colorado potato beetle Leptinotarsa decemlineata. RNA interference (RNAi) was performed using double-stranded RNAs (dsRNAs) targeting the common (dsethr) or isoform-specific (dsethra, dsethrb) regions of ethr. RNAi of dsethr, dsethra, or dsethrb by the final-instar larvae arrested larva development. The arrest was not rescued by feeding 20E. All the ethra depleted larvae stopped development at prepupae stage; the body cavity was expanded by a large amount of liquid. Comparably, more than 80% of the ethrb RNAi larvae developmentally halted at the prepupae stage. The remaining Ldethrb hypomorphs became pupae, with blackened wings and highly-expressed burs, pburs and four melanin biosynthesis genes. Therefore, ETHRA and ETHRB play isoform-specific roles in regulation of ecdysis during larva-pupa transition in L. decemlineata.